Preparation method of metal hydroxide-cellulose composite material and application of metal hydroxide-cellulose composite material in energy-saving packaging

By preparing metal hydroxide-cellulose composite materials, the problems of high energy consumption and insufficient temperature and humidity regulation of existing food storage technologies are solved, and multiple effects of energy conservation, environmental protection and food preservation are achieved.

CN119502472AActive Publication Date: 2025-02-25LUSHAN COUNTY RUFENG NEW ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411663305.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing food storage technology has high energy consumption and lacks control over temperature and humidity, resulting in food corruption and environmental pollution.

Method used

The composite material is prepared by hydrothermal reaction and electrospinning technology to form an energy-saving packaging material with packaging humidity regulation, heat dissipation and antibacterial functions.

Benefits of technology

Effectively reduce the use of cold chain equipment and plastic packaging, extend the food preservation time, reduce energy consumption for food storage, and have the advantages of environmental protection, safety and greenness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502472A_ABST
    Figure CN119502472A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and relates to a preparation method of a metal hydroxide-cellulose composite material, which comprises the following steps: preparing a zinc salt precursor reaction solution, immersing a biomass fiber-aluminum film according to a ratio of 50-100g / L of the biomass fiber-aluminum film to the precursor reaction solution, carrying out hydrothermal reaction at 60-120 DEG C for 5-10 hours, cooling, filtering, washing and drying to obtain the metal hydroxide-cellulose composite material. The biomass cellulose and metal hydroxide nanosheets are obtained; according to the material ratio of the biomass cellulose and metal hydroxide nanosheet to the sodium laurate solution being 60-120 g / L, carrying out in-situ growth to obtain a hydrophobic biomass cellulose and metal hydroxide nanosheet; and performing electrostatic spinning on the surfaces of the hydrophobic biomass cellulose and metal hydroxide nanosheets to deposit cellulose acetate, thereby obtaining the hydrophobic biomass cellulose and metal hydroxide composite nanosheets. The prepared material is applied to an energy-saving packaging material, has asymmetric infrared radiation performance, has effective humidity regulation and control, heat dissipation and bacteriostasis functions, and can be used for fresh-keeping packaging of food fresh materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, relates to energy-saving materials, and in particular to a preparation method of a metal hydroxide-cellulose composite material and application of the composite material to energy-saving packaging. Background Art

[0002] At present, most food storage technologies are still high-energy-consuming and non-energy-saving technologies, usually using high-energy-consuming methods such as refrigerators, cold storage and vacuum storage to extend the shelf life of food. It is worth noting that food spoilage caused by excessive temperature and humidity accounts for a considerable proportion. Therefore, regulating food storage temperature and humidity is of great significance to reducing food storage energy consumption and preventing food spoilage.

[0003] Packaging materials refer to materials used to produce and package various items, which are intended to ensure that the circulation, storage and transportation of products after production are more convenient and safer. Most of the existing packaging materials are made of transparent plastic materials, but plastic itself is difficult to degrade in the natural environment. Improper post-use treatment will cause environmental pollution and lack the ability to be environmentally friendly and energy-saving. At the same time, the current packaging materials lack the control of temperature and humidity during the storage of food, and cannot solve the problem of high energy consumption caused by technologies such as refrigerators, cold storage and vacuum storage. In order to reduce the high energy consumption problem caused by current food storage technology and improve the environmental protection and energy-saving characteristics of packaging materials, it is necessary to develop a new type of energy-saving packaging material.

[0004] The energy-saving packaging material prepared by the present invention is assembled from composite cellulose and metal hydroxide nanosheets, has packaging humidity control, heat dissipation and antibacterial functions, effectively reduces the use of cold chain preservation equipment and plastic products, and has good application prospects in the field of food preservation. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the first object of the present invention is to provide a method for preparing a metal hydroxide-cellulose composite material.

[0006] Technical Solution

[0007] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0008] a) preparing a 0.01-0.03 mol / L zinc salt solution, adding hexamethylenetetramine in a molar ratio of 1:1-1:3, preferably 1:2, to the zinc salt, and stirring to obtain a precursor reaction solution;

[0009] b) Pour the precursor reaction solution into a stainless steel reactor lined with polytetrafluoroethylene and press the biomass fiber

[0010] @The ratio of aluminum film to precursor reaction liquid is 50-100 g / L, immerse biomass fiber @aluminum film, hydrothermal reaction at 60-120℃ for 5-10 hours, cool, filter, wash with distilled water for 3-6 times, and heat at 80-120℃

[0011] Drying for 12 to 24 hours to obtain biomass cellulose@metal hydroxide nanosheets;

[0012] c) preparing a sodium laurate solution with a concentration of 40 to 80 g / L, and immersing the biomass cellulose@metal hydroxide nanosheets in the sodium laurate solution according to a material ratio of 60 to 120 g / L.

[0013] Metal hydroxide nanosheets, react at 50°C for 4-8h to obtain hydrophobic biomass cellulose@metal hydroxide nanosheets;

[0014] d) preparing an electrospinning solution according to a molar ratio of acetone to dichloromethane of 1:2 to 1:5, dissolving cellulose acetate in the solution to obtain a cellulose acetate electrospinning solution with a concentration of 60 to 100 g / L, and electrospinning the solution on the surface of the hydrophobic biomass cellulose@metal hydroxide nanosheets to deposit cellulose acetate, thereby obtaining a metal hydroxide-cellulose composite material.

[0015] In a preferred embodiment of the present invention, the zinc salt in step a) is one or a combination of zinc nitrate, zinc acetate or zinc chloride.

[0016] In a preferred embodiment of the present invention, the biomass fiber@aluminum film in step b) is a cellulose surface coated with high-purity aluminum or aluminum oxide.

[0017] Furthermore, when the biomass fiber @ aluminum film is a cellulose surface coated with high-purity aluminum, it is prepared by magnetron sputtering technology. The specific process is: in a nitrogen atmosphere, the Al target is loaded into a magnetron sputtering furnace, the distance between the target and the sample is adjusted to 20-40 mm, the sputtering power is 20-40 W, the time is 10-20 min, and Al particles are sputtered on the surface of the biomass fiber to obtain a biomass fiber @ high-purity aluminum film.

[0018] Furthermore, when the biomass fiber @ aluminum film is a cellulose surface coated with aluminum oxide, it is prepared by a sol-gel method, and the specific process is: prepare a solution according to a volume ratio of anhydrous ethanol and water of 1:1 to 1:2, add aluminum nitrate, and acetic acid to adjust the solution pH to 4 to 5 to prepare an aluminum sol with a concentration of 0.1 to 0.2 mol / L; then soak the biomass fiber in the aluminum sol, let it stand for 1 to 2 hours, then dry it at 60 to 120°C for 5 to 10 minutes, soak it again and dry it, and repeat 5 to 10 times to obtain a biomass fiber @ alumina film.

[0019] In a preferred embodiment of the present invention, the electrospinning in step d) has the following process parameters: an ambient temperature of 10 to 30°C, a relative humidity of 20 to 40%, an electrospinning liquid flow rate of 0.06 to 0.09 mL / min, and a distance between the needle and the collector of 10 to 15 cm.

[0020] The second object of the present invention is that the metal hydroxide-cellulose composite material prepared according to the above method is assembled from composite cellulose and metal hydroxide nanosheets, wherein the composite cellulose is composed of biomass cellulose and cellulose acetate, and the metal hydroxide nanosheets are dispersed on the surface of the biomass cellulose.

[0021] Wherein, the diameter of the biomass cellulose is 10 to 40 μm; the diameter of the cellulose acetate is 20 to 60 μm; and the size of the metal hydroxide nanosheet is 300 to 800 nm.

[0022] Furthermore, the metal hydroxide-cellulose composite material is composed of a hydrophilic cellulose acetate layer and a hydrophobic biomass cellulose@metal hydroxide nanosheet layer, and has asymmetric infrared radiation performance and asymmetric wetting performance.

[0023] Among them, the thickness of the hydrophilic cellulose acetate layer is 100-200 μm, the reflectivity is not less than 80%, and the water contact angle is not higher than 40°; the thickness of the hydrophobic biomass cellulose@metal hydroxide nanosheet layer is 500-800 μm, the emissivity is not less than 90%, and the water contact angle is not less than 120°.

[0024] The invention also discloses applying the prepared metal hydroxide-cellulose composite material to energy-saving packaging materials.

[0025] Beneficial Effects

[0026] The metal hydroxide-cellulose composite material prepared by the present invention is composed of composite cellulose. It has the advantages of being cheap, safe and green and environmentally friendly when used as an energy-saving packaging material, and can effectively reduce the use of plastic packaging products; it has asymmetric infrared radiation performance, which can effectively reduce the temperature inside the package and reduce the use of cold chain equipment; it has a directional liquid transfer function, which can adjust the humidity inside the package, alleviate food corruption caused by excessive humidity, and extend the food preservation time; it makes full use of the unique layered structure, metal ion release, positive charge layer adsorption, active oxygen release and other properties of metal hydroxide, and grows it in situ on the cellulose surface, and the obtained energy-saving packaging material has excellent antibacterial properties. The energy-saving packaging material has the functions of packaging humidity control, heat dissipation and antibacterial, and can be used for fresh-keeping packaging that can be used for fresh food materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1Scanning electron microscope images of biomass cellulose, where (a) is agricultural waste cellulose, (b) is waste paper cellulose, and (c) is waste packaging cellulose;

[0028] Figure 2 . Scanning electron microscope image of biomass cellulose @ aluminum film, where (d) is biomass fiber @ high purity aluminum film, (e) is biomass fiber @ alumina film, and (f) is biomass fiber @ aluminum-based film;

[0029] Figure 3 . Scanning electron micrographs of biomass cellulose@metal hydroxide nanosheets, (g), (h) and (i) are all biomass cellulose@zinc aluminum hydroxide nanosheets;

[0030] Figure 4 .Scanning electron microscope image of cellulose acetate;

[0031] Figure 5 .Comparison chart of food preservation performance of polyethylene packaging materials and energy-saving packaging materials. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0033] Example 1

[0034] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0035] a) preparing biomass fiber @ high purity aluminum film by magnetron sputtering technology, specifically, in a nitrogen atmosphere, loading an aluminum target into a magnetron sputtering furnace, adjusting the target distance to 10 mm, the sputtering power to 20 W, and the sputtering time to 20 min, sputtering high purity aluminum onto the surface of the biomass fiber to obtain a biomass fiber @ high purity aluminum film;

[0036] b) 1.4 g zinc nitrate and 0.57 g hexamethylenetetramine were weighed and dissolved in 60 mL deionized water, and placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, and the biomass fiber @ high purity aluminum film was vertically placed in the autoclave Teflon container until it was completely immersed, reacted at 90° C. for 10 h, and after cooling, washed with deionized water and ethanol for multiple times, and dried at room temperature for 24 h to obtain the biomass fiber @ zinc aluminum hydroxide nanosheet;

[0037] c) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion, immersing the biomass fiber @ zinc aluminum hydroxide nanosheets therein, and reacting at 50° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0038] d) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution. A layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0039] The surface morphology of biomass cellulose is shown in Figure 1 In (a), the biomass fibers are mechanically entangled together to form a network structure, and the biomass fibers are randomly oriented. In addition, the biomass fibers exhibit a large aspect ratio, which is conducive to forming a strong and flat film.

[0040] The morphology of the biomass cellulose@aluminum film is shown in Figure 2 In (d), the diameter of the biomass fibers increases, and nano-aluminum evenly covers the surface of the cellulose fibers, providing an aluminum source for the subsequent acquisition of zinc aluminum hydroxide nanosheets.

[0041] The morphology of biomass cellulose@zinc aluminum hydroxide nanosheets is shown in Figure 3 (g), the nanosheets are randomly distributed on the surface of biomass fibers, forming a honeycomb-like rough surface, which is beneficial to enhance its infrared emissivity. The morphology of cellulose acetate is shown in Figure 4 The cellulose acetate is interlaced to form a flat film. In addition, the porous structure of the cellulose acetate surface is conducive to the heat dissipation of sunlight and enhances its sunlight reflectivity.

[0042] Comparison of food preservation performance of polyethylene packaging materials and energy-saving packaging materials is shown in Figure 5 (k) On the first day, there was no significant change between the two groups. On the third day, the stems and leaves of both groups began to turn yellow. The surface of the strawberries wrapped in polyethylene packaging was slightly white, while the surface of the strawberries wrapped in energy-saving packaging materials was more shiny. By the 12th day, the strawberries wrapped in polyethylene packaging were full of mold, while the strawberries wrapped in energy-saving packaging did not have this phenomenon. In addition, corruption is similar to an infectious disease, which will accelerate the deterioration of normal food, and energy-saving packaging makes up for this defect.

[0043] Example 2

[0044] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0045] a) preparing 200 mL of a mixed solution of anhydrous ethanol and water, taking 7.50 g of aluminum nitrate and adding it to the above solution, adjusting the pH of the solution to 4 with acetic acid, preparing an aluminum sol with a concentration of 0.1 mol / L, and then soaking the biomass fiber in it, letting it stand for 1 hour, and then putting it in a 120° C. oven to dry for 5 minutes, and then soaking it in the sol again, and repeating this process 5 times to obtain a biomass fiber@alumina film;

[0046] b) 1.4 g zinc nitrate and 0.57 g hexamethylenetetramine were weighed and dissolved in 60 mL deionized water, and placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor; the biomass fiber @ alumina membrane was placed vertically in a high-pressure Teflon container until it was completely immersed, and reacted at 90° C. for 10 h; after cooling, the biomass fiber @ zinc aluminum hydroxide nanosheets were washed with deionized water and ethanol for multiple times, and dried at room temperature for 24 h;

[0047] c) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion, immersing the biomass fiber @ zinc aluminum hydroxide nanosheets therein, and reacting at 50° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0048] d) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution; a layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0049] The surface morphology of biomass cellulose is shown in Figure 1 In (b), the biomass fibers are mechanically entangled together to form a network structure, and the biomass fibers are randomly oriented. In addition, the biomass fibers exhibit a large aspect ratio, which is conducive to forming a strong and flat film.

[0050] The morphology of the biomass cellulose@aluminum film is shown in Figure 2 In (e), the diameter of the biomass fiber increases, and the nano-aluminum is evenly covered on the surface of the cellulose fiber, providing an aluminum source for the subsequent acquisition of zinc aluminum hydroxide nanosheets.

[0051] The morphology of biomass cellulose@zinc aluminum hydroxide nanosheets is shown in Figure 3 (h), the nanosheets are randomly distributed on the surface of biomass fibers, forming a honeycomb-like rough surface, which is beneficial to enhance its infrared emissivity. The morphology of cellulose acetate is shown in Figure 4 The cellulose acetate is interlaced to form a flat film. In addition, the porous structure of the cellulose acetate surface is conducive to the heat dissipation of sunlight and enhances its sunlight reflectivity.

[0052] Comparison of food preservation performance of polyethylene packaging materials and energy-saving packaging materials is shown in Figure 5 (l) On the first day, there was no significant change between the two groups. On the seventh day, the tomatoes wrapped in polyethylene packaging showed damage, while the tomatoes wrapped in energy-saving packaging materials remained shiny. By the ninth day, the difference in freshness was more obvious, demonstrating the practical application potential of energy-saving packaging materials.

[0053] Example 3

[0054] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0055] a) preparing biomass cellulose@aluminum-based packaging into biomass cellulose@zinc-aluminum hydroxide nanosheets by in-situ growth technology, specifically, weighing 1.4g zinc nitrate and 0.57g hexamethylenetetramine and dissolving them in 60mL deionized water, and placing them in a 100mL polytetrafluoroethylene-lined stainless steel reactor. The biomass fiber@aluminum-based packaging was placed vertically in a high-pressure autoclave Teflon container until it was completely immersed, reacted at 90°C for 10h, cooled, washed with deionized water and ethanol multiple times, and dried at room temperature for 24h to obtain the biomass fiber@zinc-aluminum hydroxide nanosheets;

[0056] b) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion; immersing the above-mentioned biomass fiber @ zinc aluminum hydroxide nanosheets therein, reacting at 50° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0057] c) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution. A layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0058] The surface morphology of biomass cellulose is shown in Figure 1 In (c), the biomass fibers are mechanically entangled together to form a network structure, and the biomass fibers are randomly oriented. In addition, the biomass fibers exhibit a large aspect ratio, which is conducive to forming a strong and flat film.

[0059] The morphology of the biomass cellulose@aluminum film is shown in Figure 2 In (f), the diameter of the biomass fibers increases, and nano-aluminum evenly covers the surface of the cellulose fibers, providing an aluminum source for the subsequent acquisition of zinc aluminum hydroxide nanosheets.

[0060] The morphology of biomass cellulose@zinc aluminum hydroxide nanosheets is shown in Figure 3 (i) The nanosheets are randomly distributed on the surface of biomass fibers, forming a honeycomb-like rough surface, which is beneficial to enhance its infrared emissivity. The morphology of cellulose acetate is shown in Figure 4 The cellulose acetate is interlaced to form a flat film. In addition, the porous structure of the cellulose acetate surface is conducive to the heat dissipation of sunlight and enhances its sunlight reflectivity.

[0061] Comparison of food preservation performance of polyethylene packaging materials and energy-saving packaging materials is shown in Figure 5(m) On the first day, there was no significant change between the two groups. Until the third day, grapes wrapped in polyethylene packaging showed damage, while grapes wrapped in energy-saving packaging materials remained shiny. By the ninth day, the difference in freshness was more obvious, demonstrating the practical application potential of energy-saving packaging materials.

[0062] Example 4

[0063] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0064] a) preparing biomass fiber @ high purity aluminum film by magnetron sputtering technology, specifically, in a nitrogen atmosphere, loading an aluminum target into a magnetron sputtering furnace, adjusting the target distance to 10 mm, the sputtering power to 20 W, and the sputtering time to 20 min, sputtering high purity aluminum onto the surface of the biomass fiber to obtain a biomass fiber @ high purity aluminum film;

[0065] b) Weigh 1.4g zinc acetate and 0.57g hexamethylenetetramine and dissolve them in 60mL deionized water, and put them into a 100mL polytetrafluoroethylene-lined stainless steel reactor; vertically put the biomass fiber @ high-purity aluminum film into the autoclave Teflon container until it is completely immersed, and react at 90°C for 10h; after cooling, wash with deionized water and ethanol several times, and dry at room temperature for 24h to obtain the biomass fiber @ zinc aluminum hydroxide nanosheet;

[0066] c) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion; immersing the above-mentioned biomass fiber @ zinc aluminum hydroxide nanosheets therein, reacting at 50° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0067] d) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution; a layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0068] Example 5

[0069] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0070] a) preparing 200 mL of a mixed solution of anhydrous ethanol and water, taking 7.50 g of aluminum nitrate and adding it to the above solution, adjusting the pH of the solution to 4 with acetic acid, preparing an aluminum sol with a concentration of 0.1 mol / L, soaking the biomass fiber in the sol, letting it stand for 1 hour, and then putting it in a 120° C. oven to dry for 5 minutes, and then soaking it in the sol again, repeating the process 5 times to obtain a biomass fiber@alumina film;

[0071] b) Weigh 1.4g zinc oxide and 0.57g hexamethylenetetramine and dissolve them in 60mL deionized water, and put them into a 100mL polytetrafluoroethylene-lined stainless steel reactor; vertically put the biomass fiber @ alumina film into the autoclave Teflon container until it is completely immersed, and react at 90°C for 10h; after cooling, wash with deionized water and ethanol several times, and dry at room temperature for 24h to obtain the biomass fiber @ zinc aluminum hydroxide nanosheet;

[0072] c) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion, immersing the biomass fiber @ zinc aluminum hydroxide nanosheets therein, and reacting at 5° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0073] d) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution; a layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0074] Example 6

[0075] A method for preparing a metal hydroxide-cellulose composite material comprises the following steps:

[0076] a) preparing biomass cellulose@aluminum-based packaging into biomass cellulose@zinc-aluminum hydroxide nanosheets by an in-situ growth technique, specifically, weighing 1.4 g zinc acetate and 0.57 g hexamethylenetetramine, dissolving them in 60 mL deionized water, and placing them in a 100 mL polytetrafluoroethylene-lined stainless steel reactor; vertically placing the biomass fiber@aluminum-based packaging into a high-pressure autoclave Teflon container until it is completely immersed, and reacting at 90° C. for 10 h; after cooling, washing with deionized water and ethanol for multiple times, and drying at room temperature for 24 h to obtain the biomass fiber@zinc-aluminum hydroxide nanosheets;

[0077] b) dispersing 2 g of sodium laurate in 50 mL of ethanol, stirring at 50° C. for 3 h to obtain a dispersion, immersing the biomass fiber @ zinc aluminum hydroxide nanosheets therein, and reacting at 50° C. for 6 h to obtain hydrophobic biomass cellulose @ zinc aluminum hydroxide nanosheets;

[0078] c) 4 mL of acetone and 16 mL of dichloromethane were used to prepare an electrospinning solution, 1.2 g of cellulose acetate was dissolved in the spinning solution, and the solution was stirred at room temperature for 3 h to obtain a cellulose acetate electrospinning solution; a layer of cellulose acetate was deposited on the hydrophobic biomass cellulose@zinc aluminum hydroxide nanosheets using electrospinning technology to obtain the obtained product.

[0079] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a metal hydroxide-cellulose composite material, characterized in that: The steps include: a) preparing a 0.01-0.03 mol / L zinc salt solution, adding hexamethylenetetramine in a molar ratio of hexamethylenetetramine to zinc salt of 1:1-1:3, and stirring to obtain a precursor reaction solution; b) pouring the precursor reaction liquid into a stainless steel reactor lined with polytetrafluoroethylene, immersing the biomass fiber @ aluminum membrane in a ratio of 50 to 100 g / L of the biomass fiber @ aluminum membrane to the precursor reaction liquid, hydrothermally reacting at 60 to 120° C. for 5 to 10 hours, cooling, filtering, washing with distilled water for 3 to 6 times, and drying at 80 to 120° C. for 12 to 24 hours to obtain biomass cellulose @ metal hydroxide nanosheets; c) preparing a sodium laurate solution with a concentration of 40 to 80 g / L, and immersing the biomass cellulose @ metal hydroxide nanosheets in a material ratio of 60 to 120 g / L of the biomass cellulose @ metal hydroxide nanosheets, and reacting at 50° C. for 4 to 8 hours to obtain a hydrophobic biomass cellulose @ metal hydroxide nanosheet; d) preparing an electrospinning solution with a molar ratio of acetone to dichloromethane of 1:2 to 1:5, dissolving cellulose acetate in the solution to obtain a cellulose acetate electrospinning solution with a concentration of 60 to 100 g / L, and electrospinning the solution on the surface of the hydrophobic biomass cellulose@metal hydroxide nanosheets to deposit cellulose acetate, thereby obtaining a metal hydroxide-cellulose composite material.

2. The method for preparing the metal hydroxide-cellulose composite material according to claim 1, characterized in that: In step a), the zinc salt is one or a combination of zinc nitrate, zinc acetate or zinc chloride.

3. The method for preparing the metal hydroxide-cellulose composite material according to claim 1, characterized in that: In step a), the molar ratio of hexamethylenetetramine to zinc salt is 1:

2.

4. The method for preparing the metal hydroxide-cellulose composite material according to claim 1, characterized in that: In step b), the biomass fiber@aluminum film is a cellulose surface coated with high-purity aluminum or aluminum oxide.

5. The method for preparing the metal hydroxide-cellulose composite material according to claim 4, characterized in that: In step b), the biomass fiber@aluminum film is prepared by magnetron sputtering technology when high-purity aluminum is coated on the surface of cellulose.

6. The method for preparing the metal hydroxide-cellulose composite material according to claim 4, characterized in that: In step b), when the biomass fiber@aluminum membrane is cellulose surface coated with aluminum oxide, it is prepared by a sol-gel method.

7. The metal hydroxide-cellulose composite material prepared according to any one of claims 1 to 6, characterized in that: The material is assembled from composite cellulose and metal hydroxide nanosheets, wherein the composite cellulose is composed of biomass cellulose and cellulose acetate, and the metal hydroxide nanosheets are dispersed on the surface of the biomass cellulose.

8. The metal hydroxide-cellulose composite material according to claim 7, characterized in that: The diameter of the biomass cellulose is 10 to 40 μm; the diameter of the cellulose acetate is 20 to 60 μm; and the size of the metal hydroxide nanosheet is 300 to 800 nm.

9. The metal hydroxide-cellulose composite material according to claim 7, characterized in that: The metal hydroxide-cellulose composite material consists of a hydrophilic cellulose acetate layer and a hydrophobic biomass cellulose@metal hydroxide nanosheet layer, and has asymmetric infrared radiation performance and asymmetric wetting performance.

10. An application of the metal hydroxide-cellulose composite material according to any one of claims 7 to 9, characterized in that: Apply it to energy-saving packaging materials.

Citation Information

Patent Citations

  • Biomass membrane material with both anti-ultraviolet and thermal management functions and preparation method thereof

    CN111188189A

  • Preparation method and application of cellulose double-layer film with phase change-infrared heat dissipation performance

    CN112440524A

  • Preparation method of enhanced cellulose acetate transparent composite film

    CN112795037A